The inverted syringe technique for management of inverted nipples in breastfeeding women: a pilot randomized controlled trial - Mona Nabulsi; Rayan Ghanem; Hanan Smaili; Ali Khalil (BMC, 2022)
Abstract Background Women with inverted nipples may struggle with breastfeeding and may stop exclusive breastfeeding before six months. The use of an inverted syringe to evert the nipples was successful in achieving high rates of infant latching and exclusive breastfeeding in case series but has not been tested in clinical trials. This open label, parallel group, randomized clinical trial investigated whether the use of the inverted syringe technique in women with inverted nipples would increase exclusive breastfeeding rate at one month, as compared to standard care. Methods/Design Between June 2018 and January 2020, healthy pregnant women (N=54) with grades 1 or 2 inverted nipples were randomly allocated to standard care or to an experimental group that used the inverted syringe technique to evert the inverted nipple prior to every breastfeeding. The primary outcome measure was the rate of exclusive breastfeeding at one month. Secondary outcomes included the rates of exclusive breastfeeding at three and six months, any breastfeeding at one, three, and six months, nipple eversion, successful infant latching, breastfeeding-associated complications, maternal satisfaction with breastfeeding, maternal quality of life, and adverse events. Descriptive and bivariate analyses were conducted according to the intention to treat principle. Results Participants in the experimental group were less likely to be exclusively breastfeeding at one (RR = 0.65, 95% CI: 0.44, 0.95; n = 47), and at three months (RR = 0.66, 95% CI: 0.47, 0.91; n = 45), or to practice any breastfeeding at six months (RR = 0.54, 95% CI: 0.34, 0.87; n = 44). Only 14.3% of women in the experimental group complied with the use of the inverted syringe during the first month. Breast pump and breastfeeding-associated complications were more commonly reported in the control group (p < 0.05 for both). Both groups had similar rates of nipple eversion, successful infant latching, and similar satisfaction with breastfeeding and quality of life issues. Conclusion The inverted syringe technique was not associated with improvement in breastfeeding outcomes of women with inverted nipples. Larger clinical trials are needed to confirm our findings. Trial registration ClinicalTrials.gov NCT03529630 ; Registered May 8, 2018.